2012
DOI: 10.1080/15287394.2012.690686
|View full text |Cite
|
Sign up to set email alerts
|

Wildland Smoke Exposure Values and Exhaled Breath Indicators in Firefighters

Abstract: Smoke from forest fires contains significant amounts of gaseous and particulate pollutants. Firefighters exposed to wildland fire smoke can suffer from several acute and chronic adverse health effects. Consequently, exposure data are of vital importance for the establishment of cause/effect relationships between exposure to smoke and firefighter health effects. The aims of this study were to (1) characterize the relationship between wildland smoke exposure and medical parameters and (2) identify health effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…These results are in line with those observed in previous studies: Künzli et al (2006) showed that the exposure to wildfire smoke was associated with increased eye and respiratory symptoms in a study conducted in a schoolchildren cohort of South California (USA). Other occupational studies involving firefighters showed that wildfire smoke lead to acute exacerbations of respiratory and eye symptoms (Amster et al 2013;Miranda et al 2012;Ribeiro et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…These results are in line with those observed in previous studies: Künzli et al (2006) showed that the exposure to wildfire smoke was associated with increased eye and respiratory symptoms in a study conducted in a schoolchildren cohort of South California (USA). Other occupational studies involving firefighters showed that wildfire smoke lead to acute exacerbations of respiratory and eye symptoms (Amster et al 2013;Miranda et al 2012;Ribeiro et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…Most of our subjects reported "very low" or "low" levels of smoke exposure; based on the findings of Dunn et al and Adetona et al, we can estimate that average exposure to PM2.5 was in the range of 50-300 ug/m 3 , with CO levels averaging 0.4-2 ppm across the shift [23,31]. Although these represent estimated average exposures over the course of an entire shift, instantaneous exposures could have been many times higher [31,32]. While the observed effects in the present study may therefore be attributed to exposures other than inhaled smoke, the increase in sputum macrophages with inclusions confirms an increased inhalation of airborne particulate matter compared to baseline sampling.…”
Section: Discussionmentioning
confidence: 99%
“…First, we were unable to directly measure the amount of smoke inhaled by our subjects, so we relied upon the firefighters' qualitative report of smoke exposure and inhalation and an analysis of macrophage particle inclusion in the sputum. Other investigators have examined the relationships between subjective self-reports of smoke exposure and measured levels of PM2.5 [31] and carbon monoxide (CO) [32], giving us the opportunity to make rough estimates of exposure based on our subjects' self-reports. Most of our subjects reported "very low" or "low" levels of smoke exposure; based on the findings of Dunn et al and Adetona et al, we can estimate that average exposure to PM2.5 was in the range of 50-300 ug/m 3 , with CO levels averaging 0.4-2 ppm across the shift [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of various smokes, dusts, harmful mixtures, gases, such as CO, can be very dangerous [9] . There are sometimes accidents when firemen hurry to the place of intervention [10] .…”
Section: Introductionmentioning
confidence: 99%